Analisis Semiotik Charles S. Pierce dalam Drama Drama Mangir Karya Pramoedya Ananta Toer - Humokor, Hikma Nurcahyani; Daud, Rolan K.; Sahari, Sella; Jannah, Firdha Fadhilatul; Kadir, Herson (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
This research aims to determine the results of the analysis of Pramoedya Ananta Toer's